Modelling of catalytic reactivity of inhomogeneous surfaces in monomer-monomer reactions - Skakauskas, Vladas; Katauskis, Pranas (Nonlinear Analysis: Modelling and Control, 2015)
The kinetics of a A1 + A2 -> A1A2 reaction on inhomogeneous surfaces with continuously distributed adsorption sites is investigated numerically using two phenomenological models. One of them includes: the bulk diffusion of reactants from a bounded vessel towards the adsorbent and the product bulk one from the adsorbent into the same vessel, adsorption and desorption of molecules of both reactants, and surface diffusion of adsorbed and product particles before their desorption. The other model describes surface reaction provided that concentrations of both reactants at the surface are given. Both models are based on the Langmuir–Hinshelwood reaction mechanism coupled with the Eley–Rideal step. Two surface diffusion mechanisms are used. According to one of them, the diffusion flux of the adsorbed and product particles is described by the standard Fick law, while in the other one the surface diffusion flux is based on the particle jumping into a nearest vacant adsorption site. Simulations were performed using the finite difference technique. The kinetic rate constants, Eley–Rideal steps, and surface diffusion mechanisms influence on the catalytic reactivity of surf aces is studied.